Refractory vasospastic angina in a patient with fibromuscular dysplasia: A case report. Issue 6 (June 2021) - Widmann, Maddalena; Fezzi, Simone; Pighi, Michele; Gambaro, Alessia; Ferrero, Valeria; Ribichini, Flavio
Abstract: A 49-year-old woman affected by fibromuscular dysplasia (FMD) of the carotid artery with recurrent coronary vasospasm, refractory to medical therapy was admitted for anginal pain. Coronary involvement related to FMD is uncommon and its diagnosis "in vivo" still represents a challenge. Although a clear association between FMD and spontaneous coronary artery dissections is described, the presentation as severe coronary vasospasm is rare and it is associated with unfavorable outcome, especially when treated by means of percutaneous coronary intervention. The use of intravascular ultrasound played a key role in choosing the appropriate strategy for the management of the patient. <Learning objective: During the past years fibromuscular dysplasia (FMD) has been recognized as an underdiagnosed underlying pathology possibly associated with acute coronary syndromes, especially in the setting of young women. Coronary involvement has been recently associated with vasospasm, reported in previous cases as severe refractory vasospasm. Intravascular imaging techniques are able to detect FMD structural coronary abnormalities, aiming for clinicians to choose the appropriate strategy for the management of the patient.>